Board Oversight and Dividend Policies in Malaysian Shariah-Compliant Companies - Yasmin Jamadar; Mosab I. Tabash; Mohammad Imtiaz Hossain; Mohammad Shibli Shahriar (Journal of Islamic Monetary Economics and Finance, 2024)
A stable dividend policy is often in the best interests of both the company and its shareholders. Considering the importance of dividend policy, we examine the determinants of dividend payment in Malaysian Sharia-compliant listed firms and the moderating role of board directors.  To this end, we apply a static-panel model using data of Malaysian Shariah-compliant listed firms from 2014 to 2020.  We find that ROA (Return on Asset) and Price-Earnings ratio (PER) have a significant positive impact on the dividend payout ratio (DPR). On the other hand, NAV (Net Asset Value) shows a negative and significant relationship with the DPR. Our findings also reveal that the board of directors significantly and positively influence the decision to pay dividends. The findings of the study hold significant importance for corporations in determining a suitable dividend policy that can ensure the sustainability of a consistent dividend payout and ensure their organization's financial stability, particularly in Malaysian-listed Shariah-compliant firms.